Marketing Development Model of Goyor Woven Fabric Increases Consumer Buying Interest in Pandemic Covid-19 Era: Study at Sragen Goyor Industry Center - S. Suranto; Much. Djunaidi (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
Goyor woven fabric is a product of the creative industry, a micro, small and medium enterprises (SMEs) product in weaving. Goyor woven fabric is developed industrial center locations at Kalijambe, Miri, Plupuh, Sragen. Goyor woven fabric, as a result of weaving craft, is a handmade woven fabric through a non-machine loom (ATBM). The study aims to raise the potential of woven fabric products so that woven fabric products (goyor) become attractive to consumers and increase consumer buying interest. The strategy applied to increase sales volume and increase consumer buying interest is through marketing models by marketing mix approaches 9P (products, prices, promotions, distribution, people, physic, process, public relation, and power) to consumer buying interest. This research is beneficial as a marketing development model of market-oriented goyor Woven Fabric. The research objectives are to (a) analyze woven fabric goyor products based preferred by consumers; (b) analyze the market-oriented fabric goyor marketing development model in pandemic era covid 19. The research method uses explanatory sequential methods with a research population of 15 entrepreneurs who understand Kalijambe, Miri, and Plupuh goyor woven fabric products. Data analysis Likert scale using preferences costumers while increasing product marketing uses a participatory approach. The research results showed that goyor fabric product preferred by consumers has the characteristics of using a marketing mix approach as follows: (1) product variables; (2) variable prices; (3) promotion variables; (4) place variables, (5) people, (6) physic, (7) process, (8) public relation and (9) power). The concept of strategy empowerment and market-oriented product marketing empowerment model is said to be feasible and reasonable. It can be used as a marketing development model in increasing interest in buying goyor products in the pandemic era covid 19.